THROUGH as a free aspect marker in Sign Language of the Netherlands (Linguistics in Amsterdam, 2018)
This study presents a descriptive analysis of the aspectual particle THROUGH in Sign Language of the Netherlands, based on naturalistic corpus data. The results show that THROUGH marks both continuative and habitual aspect on a wide range of lexical verbs, and can appear in varying syntactic positions (i.e., both following and preceding the main verb). These results challenge previous observations by Hoiting & Slobin (2001), who argued that THROUGH only marks aspect on lexical verbs when phonological features of the verb block aspectual modification, and that it is restricted to the syntactic position immediately following the main verb. In our data THROUGH appears to be less restricted than their analysis suggests. Further, the present study challenges the results in Oomen (2016), who found that THROUGH did not occur in her data. Finally, in the corpus data, THROUGH sometimes appears without a lexical main verb, a pattern that was not attested in previous studies. In some sentences, this is due to ellipsis of the main verb, while for others, in which THROUGH seems to function as a lexical verb itself, it will be argued that THROUGH might be in the process of degrammaticalization.